ART AND COMPOSITIONAL SIGNS OF A WOMEN'S SUIT OF THE 1940'S AS A CREATIVE SOURCE FOR THE DESIGNING OF A MODERN CLOTHING COLLECTION - Струмінська, Т. В.; Прасол, С. І.; Гальчинська, О. С.; Ровенець, О. І. (Art and Design, 2019)
Determination of the peculiarities of the shape, structure and color of a women's costume of the 40's of the twentieth century. for designing collections of modern women's clothing. The methodological basis of the article form a comparative-historical method, which allowed to reveal the dynamics of the development of artistic and constructive solutions of silhouettes; a method of figurative and stylistic analysis in the study of artistic compositional features of women's costume; structural-functional method of analysis in determining the recommendations for designing a collection of women's clothing in costume stylistics of the 40's of the twentieth century. The analysis of fashion trends of women's clothing of the first and second half of the 40-s of XX century was carried out taking into account the influence of military events on fashion; special features are structured, the structural arrangement is characteristic of women's clothes of those times, features are distinguished: silhouette, constructive and decorative elements, color scheme of women's costumes, recommendations for designing a collection of women's clothing in costume stylistics of those years. The scientific novelty consists in the identification and systematization of the characteristic features inherent in women's clothing of the first and second half of the 1940's, with their subsequent use in the design process of a collection of modern clothing. The practical significance of the research carried out is to determine the stylistic features of the women's costume of the 1940's as a creative source; development and performance in the material, taking into account modern fashion trends, collection of women's clothing in the style of 40's of the 20th century; research results can be used in the development of educational programs and methodological literature on the history of costume and fashion design costumes, design history, etc.